"I was sold like an oil barrel": the social and emotional impacts of trafficking on women from the Horn of Africa - Ramos, M. (International Conference - The Current Refugees Crisis and Beyond: Narratives and Itineraries, 2016)
Female migratory flows from the Horn of Africa are mainly directed to Arabic countries and tend to take the form of legal temporary migration. As their Asian counterparts, these girls and women are subject to various degrees of trafficking and even enslavement, working mainly as in-house maids in affluent Arab households, where tend to be denied free and fair labour rights, under a harsh interpretation of the kafala, or "sponsorship" system, prevalent in Arabic countries. Although there are signs of improved legal protection in accord with international labour rules, the system in place, and the culture that supports it, imposes a tense situation where maids are subject to a reality of everyday “structural violence” and employers have to bear an unwonted responsibility. This trafficking and labour system isn’t that unfamiliar to females from the Horn, as internal female migration from rural to urban settings implies similar conditions, albeit without the benefit of a common language and a common culture. The psychological, social and economic costs of this migration are well documented but there's still a lack of understanding of the trends of female agency that emerges as direct reflection from the hardships of such forms of migration. This chapter reflects on this situation and in particular on the ways it is understood and managed both in the hosting countries and at home.